2017
DOI: 10.1002/brb3.853
|View full text |Cite
|
Sign up to set email alerts
|

Higher extrinsic and lower intrinsic connectivity in resting state networks for professional Baduk (Go) players

Abstract: IntroductionDedication and training to a profession results in a certain level of expertise. This expertise, like any other skill obtained in our lifetime, is encoded in the brain and may be reflected in our brain's connectome. This property can be observed by mapping resting state connectivity. In this study, we examine the differences in resting state functional connectivity in four major networks between professional “Baduk” (Go) players and normal subjects.MethodsResting state fMRI scans were acquired for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…The brain is not a static structure. An increasing number of neuroimaging studies have suggested the notion that cognitive training can result in substantial changes in functional activity and structure of the brain, which may contribute to cognitive benefits in the trained and untrained tasks ( Klingberg, 2010 ; Gong et al, 2015 ; Benz et al, 2016 ; Sohn et al, 2017 ). AMC, a specific skill learning that involves the co-activation of multiple brain regions ( Hanakawa et al, 2003 ; Chen et al, 2006 ; Ku et al, 2012 ), can also produce functional and structural changes in the brain that may account for AMC-related cognitive enhancements.…”
Section: Neural Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…The brain is not a static structure. An increasing number of neuroimaging studies have suggested the notion that cognitive training can result in substantial changes in functional activity and structure of the brain, which may contribute to cognitive benefits in the trained and untrained tasks ( Klingberg, 2010 ; Gong et al, 2015 ; Benz et al, 2016 ; Sohn et al, 2017 ). AMC, a specific skill learning that involves the co-activation of multiple brain regions ( Hanakawa et al, 2003 ; Chen et al, 2006 ; Ku et al, 2012 ), can also produce functional and structural changes in the brain that may account for AMC-related cognitive enhancements.…”
Section: Neural Plasticitymentioning
confidence: 99%
“…For instance, working memory training has been suggested to improve performance in untrained working memory ( Holmes et al, 2009 ); video-game training has been reported to improve performance in visual attention and executive control ( Strobach et al, 2012 ; Belchior et al, 2013 ); musical training and chess or go games playing that require a broad range of cognitive skills, have been found associated with superior performance in multiple cognitive tasks including working memory, executive control and reasoning ( Kim et al, 2014 ; Benz et al, 2016 ; Burgoyne et al, 2016 ; Sala et al, 2017 ). Moreover, all the above cognitive training programs have been reported to produce functional and structural changes in the brain that may provide a neurophysiological basis for the cognitive transfer ( Klingberg, 2010 ; Gong et al, 2015 ; Benz et al, 2016 ; Sohn et al, 2017 ). Although the findings are promising, it should be noticed that many existing training programs are constrained by the fact that they are conducted under controlled laboratory settings, which may pose difficulties in generalizing the obtained findings to broader contexts and real-world situations ( Klingberg, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Specific regions have long been believed to form the basis of cognitive expertise in board games. However, from the investigation of functional connectivity between the caudate and the default mode network (DMN) ( Duan et al, 2012a ), step-by-step exploration of specific region-based functional connections was applied ( Duan et al, 2014 ; Sohn et al, 2017 ; Song et al, 2020 ; Wang et al, 2020 ). Recently, whole-brain-based detection of brain functional connectivity was reported as a dynamic functional network characteristic of Chinese chess experts ( Premi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, competitive online gaming often requires players to coordinate sensory and motor control to accomplish their tasks and win against competitors (Anderson, Bothell, Fincham, & Moon, 2016; Sohn, Lee, Kwak, Yoon, & Kwon, 2017). Brain regions, such as the cerebellum (involved in processing automatic or highly learned motoric behaviors and coordinating control), the thalamus (a neurocircuitry hub coordinating auditory, visual, and somatosensory functions), and the brain stem (with ascending and descending pathways involved in sensory and motoric processes), have been implicated in sensory and motor processes and their coordination (Katsyri et al., 2013; Koepp et al., 1998).…”
Section: Introductionmentioning
confidence: 99%